If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + 2 + x = 2x + 9 Combine like terms: 12 + 2 = 14 14 + x = 2x + 9 Reorder the terms: 14 + x = 9 + 2x Solving 14 + x = 9 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 14 + x + -2x = 9 + 2x + -2x Combine like terms: x + -2x = -1x 14 + -1x = 9 + 2x + -2x Combine like terms: 2x + -2x = 0 14 + -1x = 9 + 0 14 + -1x = 9 Add '-14' to each side of the equation. 14 + -14 + -1x = 9 + -14 Combine like terms: 14 + -14 = 0 0 + -1x = 9 + -14 -1x = 9 + -14 Combine like terms: 9 + -14 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5
| 2+3(0-1)=0-1 | | 5a-5=-3(-a-1) | | 6x+4=58 | | x^2+10.8x-0.6=0 | | solvex^2+10.8x-0.6=0 | | -1+9-6(1)=12-7(1)-3 | | 5x/6x= | | v^6-64=0 | | x^2+10.8x+0.6=0 | | 0.2b^2+15b-150=0 | | 23-4x=11+8x | | -4y-(5y+6)=3 | | 5/6(7-2)+1/3 | | -5(2x-8)+3x=52 | | 12+2x-6=x+15 | | 12+2x-6=x+16 | | 5x+3=6x+9 | | 3+5q=x+15 | | 4x^3-6x^2-24x= | | .5d+3d+5=0 | | 4.8x-12=3.4x-5 | | -11=4-5(2p+11) | | 10x+3=12x-11 | | (15a^3)-(3a)=0 | | 8z-7=3z-7-5 | | 14x-8-3x-9-x+18= | | 7x(4*6)= | | X+2=-x+20-4x | | 7*1/2 | | 16-8y=4y | | -9+3x+9z-93-z-7x= | | 4/9x=2/3 |